2021
DOI: 10.3390/ani11102941
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Termite-Fishing Tasks as Enrichment for Sanctuary-Housed Chimpanzees: Behavioral Effects and Impact on Welfare

Abstract: Artificial termite-fishing tasks are a common enrichment for captive great apes, promoting species-typical behaviors. Nonetheless, whether these activities are linked to changes in other behaviors and whether these changes persist over time has seldom been investigated. We assessed whether the use of an artificial termite-fishing task was linked to changes in the solitary behavior and social dynamics in two groups of sanctuary-housed chimpanzees (Pan troglodytes). Specifically, we compared chimpanzee behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 92 publications
1
13
0
Order By: Relevance
“…In contrast to previous studies (e.g., Brent and Eichberg 1991), however, interacting with the enrichment did not disrupt the occurrence of usual social activities. Thus, our results are in line with those reported by Yamanashi et al (2016) and Padrell et al (2021), who also found no changes in the occurrence of affiliative behaviors resulting from toolbased enrichments. Nonetheless, we did find a positive association between participation and agonistic behaviors, which increased across sessions.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to previous studies (e.g., Brent and Eichberg 1991), however, interacting with the enrichment did not disrupt the occurrence of usual social activities. Thus, our results are in line with those reported by Yamanashi et al (2016) and Padrell et al (2021), who also found no changes in the occurrence of affiliative behaviors resulting from toolbased enrichments. Nonetheless, we did find a positive association between participation and agonistic behaviors, which increased across sessions.…”
Section: Discussionsupporting
confidence: 94%
“…Complexity, predictability, controllability, and novelty can all influence the impact of enrichment devices on animal welfare; enrichment objects that are biologically relevant, account for an animal’s behavioral ecology, and elicit natural behaviors may be particularly effective [ 4 , 5 ]. To ensure that enrichment objects are improving an animal’s welfare, researchers and animal caregivers often observe and compare primates’ activity levels and behaviors before and after objects are provided (e.g., [ 8 , 9 , 10 , 11 ]). For example, artificial termite-fishing tasks decreased inactivity and increased tool use in captive chimpanzees [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that enrichment objects are improving an animal’s welfare, researchers and animal caregivers often observe and compare primates’ activity levels and behaviors before and after objects are provided (e.g., [ 8 , 9 , 10 , 11 ]). For example, artificial termite-fishing tasks decreased inactivity and increased tool use in captive chimpanzees [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations